(3GdeYde HahGFO eSdes - (3CHh YHO Gddg eMeO Hf Ydj Hf YeQ GdJejei GdeGRQis; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efRd GdCMcGe eaUd GdMdGd hGdMQGe gPG cJGH bUO ajg Edi JYdjb eGLQi ai eLGdS Gdabjg GdeGRQi cJGH eSde gPG ef CUM cJH GdMOjK s
(3BNQgG (B:s
(3Qhi GddjK Hf SYO MOKfi LYaQ Hf QHjYI Yf YHO GdQMef Hf gQeR GdMOjK ced GdSaQ GdChd ef ef GdeYde hGdMeO ddg Mb MeOg s
(3GdfSNI HgG MhGTs
(3HgG BKGQ JbWjYs
(3cJHJ HNW ajg HYV GdVHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs